1966
DOI: 10.5254/1.3544847
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Fatigue Limit for Rubber

Abstract: synopsisInvestigations of the dynamic cut growth behavior of vulcanized rubbers indicate that there is a minimum tearing energy a t which mechanical rupture of chains occurs. The limiting value is characteristic of each vulcanizate, but is in the region of 0.05 kg./cm. The mechanical fatigue limit, below which the number of cycles to failure increases rapidly, is accurately predicted from this critical tearing energy. Characteristics of cut growth at low tearing energies, and effects of polymer, vulcanizing sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 0 publications
4
77
0
Order By: Relevance
“…5b). When G is relatively small, the extension of crack per cycle dc/dN varies almost linearly with G. As G increases, dc/dN increases steeply, becoming a higher order polynomial function of G. Such behavior is similar to the fatigue fracture of elastomers [30,31,34].…”
Section: Characterization Of Fatigue Fracturementioning
confidence: 52%
See 1 more Smart Citation
“…5b). When G is relatively small, the extension of crack per cycle dc/dN varies almost linearly with G. As G increases, dc/dN increases steeply, becoming a higher order polynomial function of G. Such behavior is similar to the fatigue fracture of elastomers [30,31,34].…”
Section: Characterization Of Fatigue Fracturementioning
confidence: 52%
“…Fatigue fracture of tough hydrogels, however, has remained unexplored. This lack of information on fatigue fracture of tough hydrogels hinders their further development, knowing that fatigue fracture is a critical mode of failure of all other tough materials, including metals, plastics, elastomers and composites [26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…When rubber is under multiaxial stresses, Mars2 suggested that the energy required to tear a crack is the cracking energy density, W C , in the above expression of the energy release rate to determine their fatigue crack growth rate, dc / dn . The effects of energy release rate on the fatigue crack growth rate of rubbery materials were reported by Lake and Lindley 9–11. Under cyclic tensile loading with a zero stress ratio, the fatigue crack growth rate of rubber with respect to various energy release rates is divided into four regimes,12 as schematically illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 89%
“…The effects of energy release rate on the fatigue crack growth rate of rubbery materials were reported by Lake and Lindley. [9][10][11] Under cyclic tensile loading with a zero stress ratio, the fatigue crack growth rate of rubber with respect to various energy release rates is divided into four regimes, 12 as schematically illustrated in Figure 1. When the energy release rate is above the smallest value of G z around 10 À4 KJ/m 213 and below a threshold value, G 0 , the fatigue crack growth rate, dc/dn, in Regime 1 is much slower and remains almost constant, depending on the ozone concentration in atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…For such relaxing conditions and T < T dc dU -f(T) (1) where c is the crack length at number of cycles N. There is a minimum value of 7", (T o ) below which no mechanical fatigue crack growth will occur [4]. during that cycle.…”
Section: Crack Growth and Fatigue In Rubbermentioning
confidence: 99%